Sequencing of game complexes in women’s volleyball: are there differences according to the set played? - Cavalcante Vieira, Pedro Henrique; Laporta, Lorenzo; Ferreira Pedrosa, Gustavo; De Paula Santana, Gusto Faria; Barreiros Freire, Auro; Couto Rangel, Crislaine; Barbosa de Lira, Claudio Ande; Clemente, Filipe Manuel; Leonardi, Thiago Jose; De Conti Teixeira Costa, Gustavo (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. The objective of the present manuscript was to analyse the flow of play in high-level women’s volleyball by sequencing game complexes per set.Methods. The sample analysed 135 matches played in the 2021/2022 Brazilian Women’s Superliga, with the number of matches analysed ranging from 14 and 25 matches for all teams participating in the championship. Eigenvector Centrality and Social Network Analysis conducted the connectivity and specificity of relationships as, and inferential analysis was performed using the chi-square test with a Monte Carlo correction.Results. The results showed that the highest eigenvalues were for the continuity effect, except for complex 0. Regarding the continuity effect, the eigenvalues in the first four sets were higher for complexes III, IV, and V. In the fifth set, the highest eigenvalues were close between complexes II, III, IV, and V for the continuity effect. Furthermore, the results indicated that there was no association between the sequencing of game complexes and the set played ( ² = 2470.01 and = 0.34, p = 0.272), nor between the number of complexes and the set played ( ² = 17.63 and = 0.03, p = 0.346).Conclusions. In conclusion, women’s volleyball presents gameplay strategies to sustain play, promoting game continuity, regardless of the set played. The number of game complexes required to secure a point varies between two and three game complexes. Coaches should consider the dynamics in women’s volleyball matches, preparing teams for less risky and more continuous play.
Keywords: performance analysis; attack; counter-attack; offensive structuring